Acceptability of OP/Na swabbing for SARS-CoV-2: a prospective observational cohort surveillance study in Western Australian schools. Issue 1 (26th January 2022) - Thomas, Hannah M; Mullane, Marianne J; Ang, Sherlynn; Barrow, Tina; Leahy, Adele; Whelan, Alexandra; Lombardi, Karen; Cooper, Matthew; Stevenson, Paul G; Lester, Leanne; Padley, Andrea; Sprigg, Lynn; et al.
Abstract : Objectives: When the COVID-19 pandemic was declared, Governments responded with lockdown and isolation measures to combat viral spread, including the closure of many schools. More than a year later, widespread screening for SARS-CoV-2 is critical to allow schools and other institutions to remain open. Here, we describe the acceptability of a minimally invasive COVID-19 screening protocol trialled by the Western Australian Government to mitigate the risks of and boost public confidence in schools remaining open. To minimise discomfort, and optimise recruitment and tolerability in unaccompanied children, a combined throat and nasal (OP/Na) swab was chosen over the nasopharyngeal swab commonly used, despite slightly reduced test performance. Design, setting and participants: Trialling of OP/Na swabbing took place as part of a prospective observational cohort surveillance study in 79 schools across Western Australia. Swabs were collected from 5903 asymptomatic students and 1036 asymptomatic staff in 40 schools monthly between June and September 2020. Outcome measures: PCR testing was performed with a two-step diagnostic and independent confirmatory PCR for any diagnostic PCR positives. Concurrent surveys, collected online through the REDCap platform, evaluated participant experiences of in-school swabbing. Results: 13 988 swabs were collected from students and staff. There were zero positive test results for SARS-CoV-2, including no false positives. Participants reported high acceptability: 71% of students reported no or minimal discomfort and most were willing to be reswabbed (4% refusal rate). Conclusions: OP/Na swabbing is acceptable and repeatable in schoolchildren as young as 4 years old and may combat noncompliance rates by significantly increasing the acceptability of testing. This kind of minimally-invasive testing will be key to the success of ongoing, voluntary mass screening as society adjusts to a new 'normal' in the face of COVID-19. Trial registration number: Australian New Zealand Clinical Trials Registry—ACTRN12620000922976.